2017
DOI: 10.1073/pnas.1701816114
|View full text |Cite
|
Sign up to set email alerts
|

In situ characterization of cofacial Co(IV) centers in Co 4 O 4 cubane: Modeling the high-valent active site in oxygen-evolving catalysts

Abstract: The Co 4 O 4 cubane is a representative structural model of oxidic cobalt oxygen-evolving catalysts (Co-OECs). The Co-OECs are active when residing at two oxidation levels above an all-Co(III) resting state. This doubly oxidized Co(IV) 2 state may be captured in a Co(III) 2 (IV) 2 cubane. We demonstrate that the Co(III) 2 (IV) 2 cubane may be electrochemically generated and the electronic properties of this unique high-valent state may be probed by in situ spectroscopy. Intervalence charge-transfer (IVCT) band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 55 publications
7
106
0
Order By: Relevance
“…Such an electronic structure has been generally correlated to high oxygen evolution activity (70). Mechanistically, in such a structure, electronic excitations create oxygen holes (Mn n -O → Mn n−1 -O • ), forming highly reactive oxyl radicals, which are known to be critical intermediates in the proton-coupled electron transfer transformation of H 2 O to O 2 (71)(72)(73)(74)(75)(76) and in the proposal of reductive coupling (77,78) and excess charging in Li batteries (79). The generation of oxyl radicals resulting from a high lying O2p valence band, with the population of oxygen radicals inversely proportional to the size of the HOMO-LUMO energy gap, is an emerging precept for the origin of enhanced OER activity in oxidic metal catalysts (80).…”
Section: Discussionmentioning
confidence: 99%
“…Such an electronic structure has been generally correlated to high oxygen evolution activity (70). Mechanistically, in such a structure, electronic excitations create oxygen holes (Mn n -O → Mn n−1 -O • ), forming highly reactive oxyl radicals, which are known to be critical intermediates in the proton-coupled electron transfer transformation of H 2 O to O 2 (71)(72)(73)(74)(75)(76) and in the proposal of reductive coupling (77,78) and excess charging in Li batteries (79). The generation of oxyl radicals resulting from a high lying O2p valence band, with the population of oxygen radicals inversely proportional to the size of the HOMO-LUMO energy gap, is an emerging precept for the origin of enhanced OER activity in oxidic metal catalysts (80).…”
Section: Discussionmentioning
confidence: 99%
“…Among these methods, the coupling effect can play an enormous role in the modification of electronic structure and conductivity of an electrocatalyst, in which enhanced OER and ORR activities can arise from the as‐synthesized materials due to the synergetic effect between Co and Ni (Figure b,c). Furthermore, the active sites for OER activity of multivalent Co (Co 2+ , Co 3+ , or Co 4+ ) are still unclear, and although different research groups have suggested that different surface states, such as Co 2+ , Co 3+ , or Co 4+ can potentially be the OER active sites, reaction mechanisms as well as the active surface of Co require further investigation. Researchers have reported that in the normal spinel crystal structure of Co 3 O 4 with a close‐packed face‐centered cubic configuration in which Co 2+ ions occupy the tetrahedral A sites and Co 3+ ions occupy the octahedral B sites, exposed active sites associated with cations possessing higher oxidation states (Co 3+ ions) can play a dominant role as ORR active sites .…”
Section: Advancements Of Tm‐based Electrocatalystsmentioning
confidence: 99%
“…In particular, irradiation of a Ru(bpy) 3 2+ /S 2 O 8 2– solution in the presence of the initially diamagnetic cubane (all cobalt centers in oxidation state III), induces the rising of a signal with axial line shape ( g ⊥ = 2.33 and g ∥ = 2.07) . This is ascribed to the one‐electron oxidized form of the cubane (known also as “cubium”), characterized by a S = 1/2 and a formal Co(III) 3 Co(IV)‐oxo core, although the spin character is equally distributed among the four metal centers , . This evidence complements the kinetic information obtained by flash photolysis, and discussed in paragraph 3, on electron transfer from cubane to Ru(III).…”
Section: Photogenerated Woc Intermediatesmentioning
confidence: 99%